(untitled) (Journal of humanities and social sciences exploratio, 2026)
As the pinnacle of classical Chinese literature, A Dream of Red Mansions features dream depictions with unique artistic value. This paper delves into the dream depictions in A Dream of Red Mansions and their symbolic significance, aiming to uncover the crucial role dreams play in the novel. The research indicates that dream depictions in A Dream of Red Mansions can be classified into three categories: mysterious dreams, dreams reflecting reality, and symbolic dreams. These dreams hold symbolic meanings such as reflecting the inner worlds of characters, revealing their fates, foreshadowing the development of the story, reflecting phenomena in feudal society, and exposing social contradictions. Meanwhile, dream depictions make significant contributions to character portrayal, advancing the plot, and deepening the thematic ideas, enhancing the novel’s artistic charm and aesthetic value. This paper summarizes the characteristics and value of dream depictions and looks forward to future research directions, including psychological interpretations, comparative studies with other literary works, exploration of their relationship with socio-cultural backgrounds, and interdisciplinary research, with the aim of providing new ideas and perspectives for the study of A Dream of Red Mansions.